PERENCANAAN STRATEGIS SISTEM INFORMASI TERINTEGRASI PADA UNIVERSITAS MUHAMMADIYAH BENGKULU UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF - Dandi Sunardi; Ema Utami; Sudarmawan Sudarmawan (Informasi Interaktif, 2017)
The application of SI/TI in the Organization has three main objectives to improve work efficiency, effectiveness of management and competitive advantage. Planning of integrated information system strategy very important is done at the Muhammadiyah University of Bengkulu, so can having a mechanism applying SI/TI to optimal achieve the vision, mission and purpose. Limitations of this research is variable (1) the research is limited to the scope of the integrated information system strategic planning carried out at UMB, (2) The methodology used is Ward and Peppard with the method of analysis is value chain, SWOT and McFarlan Stragic Grid, (3) Data obtained through observation, interviews, documentation, and questionnaires, (4)  This research will devise a strategic information system with the final results of the research in the form of recommendations and roadmap information system implementation of integrated information system of the future at UMB. Keywords : Planning, Strategic, Integrated informaton System, Ward and Peppard, Value Chain, SWOT, McFarlan Strategic Grid.